Impact of Coal Mining on Ambient Air in Respect of Global Warming: A Critical Approach - Nimai Chandra Saha; Dibyendu Saha (Indonesian Journal of Social and Environmental Issues (IJSEI), 2023)
Coal mining is the prime reason behind climate change and has a great impact on global warming as coal produces 39℅ global CO2 emissions. At the same time, coal production is the chief factor of 40% of the world’s electricity including economic development. The purpose of the present study is to the worldwide, national & endemic impact of coal mining on ambient air in respect of global warming.  A number of peer-reviewed, research articles, reviews, and reports were collected from 1970 to 2022 employing a keyword-based search. The articles compiled were analyzed globally & indigenously and assorted according to the selected browsers addressed & the methodological approach adopted. Coal mining activities emit toxic gases into the atmosphere and hence decline the ambient air quality. The crucial Greenhouse gases contribute to the overall warming of the earth. Coal continues to be the distinctive and long-term resource of the world energy supply hence its mining-related pollution mitigation and the reclaiming of the environment are necessary. In present circumstances, it is obligatory to implement Clean Coal Technologies i.e. sustainability in energy production & its utility. Abandoned mine wasteland restored and converted into vegetative land may also solve numerous major issues like lessening GHGs, GW, and prevention of degraded wasteland.